Revitalizing Breath: Ayurvedic Insights into Bronchial Asthma Management via Vamana Karma (AYUSHDHARA, 2025)
Bronchial Asthma is a disease characterized by episodic airway obstruction and hyper responsiveness, accompanied by airway inflammation. Bronchial Asthma is compared with Tamaka Shwasa that affects the Pranavaha Srotas and characterized by Deergha shwasa, Ghurgurka, Shwasa krichhrata, which is Pranaprapeedaka in nature. It is a Kaphavataja Vyadhi for which Vamana Karma is said to be the best line of treatment, specifically in Vega kaala. Material and methods- In this case, a 33-year-old female patient who is not a known case of diabetes mellitus or hypertension, but a known case of bronchial asthma, complained of wheezing, chest tightness, and breathing difficulty for past one year, Vamana Karma was administered to the patient with Madanaphala pippali yoga. Assessment was done on symptoms of Tamaka Shwasa and Bronchial Asthma along with serum IgE levels before and after the treatment. Results- Significant reduction in clinical symptoms like wheezing, chest tightness and breathing difficulty along with serum IgE levels were noted after Vamana Karma. Conclusion- Panchakarma offers a comprehensive approach to detoxification, particularly for complex and chronic condition like Tamaka Shwasa. Vamana Karma is essential for addressing the underlying pathology, by effectively eliminating the vitiated doshas from the body and subsequently incorporating the Shamanoushadhi can enhance their recovery and significantly reduce the likelihood of relapse.